2022
DOI: 10.3389/fphar.2022.857956
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol: An Update on Its Hepatoprotective Properties and the Linked Molecular Mechanisms

Abstract: The liver plays an important role in glucose and lipid homeostasis, drug metabolism, and bile synthesis. Metabolic disorder and inflammation synergistically contribute to the pathogenesis of numerous liver diseases, such as metabolic-associated fatty liver disease (MAFLD), liver injury, and liver cancer. Celastrol, a triterpene derived from Tripterygium wilfordii Hook.f., has been extensively studied in metabolic and inflammatory diseases during the last several decades. Here we comprehensively review the phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…ConA‐induced hepatitis is characterized by acute immune responses with rapid infiltration of various immune cells and an explosive release of cytokines 23 . It has been previously reported that celastrol effectively suppressed the inflammatory response in liver injury induced by other chemicals 10 . Therefore, we investigated the effects of celastrol on ConA‐induced hepatitis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ConA‐induced hepatitis is characterized by acute immune responses with rapid infiltration of various immune cells and an explosive release of cytokines 23 . It has been previously reported that celastrol effectively suppressed the inflammatory response in liver injury induced by other chemicals 10 . Therefore, we investigated the effects of celastrol on ConA‐induced hepatitis.…”
Section: Resultsmentioning
confidence: 99%
“…The progression of ConA‐induced hepatitis is involved with the infiltration of a great number of cytokines, leading to liver injury, including hepatocyte apoptosis and necrosis 27–30 . Previous studies demonstrated that celastrol played a protective role in APAP‐induced, ANIT‐induced, and CCL4‐induced liver injuries by inhibiting proinflammatory responses 10 . Here, we investigated the effect of celastrol on ConA‐induced hepatitis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Celastrolis a natural triterpenoid found in Tripterygium wilfordii that has been used to treat a variety of common diseases because of its strong anti-inflammatory activity ( Jing et al, 2021 ; Zhu et al, 2021 ; Li M. et al, 2022 ). Celastrol can inhibit the upregulation of IL-6andTNF-α expression in NP cells induced by IL-1β ( Chen et al, 2017 ).…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 99%
“…In addition to its role in digestion, the liver is involved in the biochemical processes of development, nutrition, energy production, and reproduction. It contributes to carbohydrate and fat metabolism, bile secretion, and vitamin storage [ 2 ]. The liver disease is still one of the significant threats to public health and a global problem because of these functions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%